Geocomputation a practical primer - Brunsdon, Chris; Singleton, Alex (SAGE, 2015)
The only student focused, applied primer for Geocomputation in the social sciences. With example code and data sets provided as add-ons, it enables readers to work through all the examples themselves. An accessible text, specifically designed for readers who are new to Geocomputation as an area of research.